2013
DOI: 10.1177/1933719113488450
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Histone Deacetylase 1, But Not Other Class I Histone Deacetylases, Is Significantly Increased in Endometriosis

Abstract: Class I histone deacetylases (HDACs-1-3) play an important role in steroid hormone-dependent gene expression and in modulating cell survival and proliferation. We analyzed their expression in a tissue microarray including 74 endometriosis samples and 30 normal endometrium controls. The mean HDAC-1 immunoreactivity score (IRS + standard deviation) was 7.6 + 2.5 in endometriosis and 5.3 + 2.3 in normal endometrium (P < .001). In contrast, the IRSs of HDAC-2 and -3 were 11.7 + 0.7 and 11.8 + 1.1 in endometriosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 30 publications
7
29
1
3
Order By: Relevance
“…First, a global H3K4 and H3K9 hypomethylation in endometriotic lesions has been reported recently [ 37 ]. In addition, global H3 hypoacetylation as well as HDAC1 overexpression also have been reported [ 17 , 38 , 39 ]. While selective inhibition of prostaglandin E2 receptors EP2 and EP4 is shown to have many desirable therapeutic effects [ 40 ], it has no effect on LSD1 expression in endometriotic lesions [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, a global H3K4 and H3K9 hypomethylation in endometriotic lesions has been reported recently [ 37 ]. In addition, global H3 hypoacetylation as well as HDAC1 overexpression also have been reported [ 17 , 38 , 39 ]. While selective inhibition of prostaglandin E2 receptors EP2 and EP4 is shown to have many desirable therapeutic effects [ 40 ], it has no effect on LSD1 expression in endometriotic lesions [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the levels of HDAC1 and/or HDAC2, two of the most abundant HDACs in human cells, were deregulated in endometriotic stromal cells. While one study reported that both HDAC1 and HDAC2 were upregulated in endometriotic stromal cells, two other studies reported the upregulation of HDAC1 and HDAC2 . Nevertheless, the expression of HDAC1 and HDAC2 were induced by the steroid hormones, 17β‐estradiol and progesterone, a notion that is consistent with the central role of steroid hormones in the development of endometriosis (Figure ).…”
Section: Alteration Of the Histone Code In Endometriosismentioning
confidence: 52%
“…This observation was confirmed by the reported higher expression of HDAC1 and HDAC2 genes and lower levels of SIRT1 in the endometriotic lesions of affected women in comparison with normal endometrium. Moreover, in ectopic implants, the loss of HDAC expression modulation by estrogen and progesterone was reported [128,129,136]. Studies concerning histone modification are still scarce and heterogeneous in results, method, and study design.…”
Section: Epigenetic Histone Modificationsmentioning
confidence: 99%